1997
DOI: 10.2527/1997.751258x
|View full text |Cite
|
Sign up to set email alerts
|

The use of electrolyte solutions for reducing transport stress.

Abstract: The transport and handling procedures imposed on beef cattle during the normal course of marketing can be a significant stressor. Factors including time off feed, water deprivation, mixing and the resulting behavioral problems, transport movement, unfamiliar noise, inclement weather, and so forth are often present and collectively result in live weight and carcass losses as well as degraded meat quality. In addition, a growing public concern regarding animal welfare in such situations is evident. Understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
1
11

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 49 publications
10
112
1
11
Order By: Relevance
“…These physiological responses were similar to those recorded in cattle in response to transport in previous studies (Murata andHirose 1990, 1991;Tarrant et al 1992;Schaefer et al 1997;Jacobson and Cook 1998;Knowles 1999). Furthermore, similar results were found in habituation studies on cattle, where repeated transport resulted in decreased cortisol levels (Locatelli et al 1989) and heart rate (Jacobson and Cook 1998).…”
Section: Discussionsupporting
confidence: 76%
“…These physiological responses were similar to those recorded in cattle in response to transport in previous studies (Murata andHirose 1990, 1991;Tarrant et al 1992;Schaefer et al 1997;Jacobson and Cook 1998;Knowles 1999). Furthermore, similar results were found in habituation studies on cattle, where repeated transport resulted in decreased cortisol levels (Locatelli et al 1989) and heart rate (Jacobson and Cook 1998).…”
Section: Discussionsupporting
confidence: 76%
“…Stressors increase the percentage of neutrophils and decrease the percentage of lymphocytes in the leukogram, which leads to changes in the N : L ratio (Schaefer et al, 1997). For this reason, the N : L ratio is regarded as an important indicator of stress response in animals (Miranda-de la Lama et al, 2010;Ekiz et al, 2012a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The use of pre-slaughter supplements, largely consisting of mixtures of sugars and electrolytes, has also been investigated for their attenuating effects on transport stress (see review by Schaefer et al 1997). Commercial feed supplements or soluble preparations are now available and these can be can be provided either on farm immediately before transport or while in lairage.…”
Section: Pre-slaughter Supplementsmentioning
confidence: 99%
“…Commercial feed supplements or soluble preparations are now available and these can be can be provided either on farm immediately before transport or while in lairage. Schaefer et al (1997) reported that the administration of these supplements to cattle resulted in reduced losses in live and carcass weights and reduced incidence of dark cutting. The results of Australian research, while encouraging, have been relatively inconclusive .…”
Section: Pre-slaughter Supplementsmentioning
confidence: 99%